SPEECH STYLES PERFORMED BY THE HOSTS OF “MASTERCHEF INDONESIA SEASON 3” COOKING TALENT SHOW - PRATIWI, ANGGIT (Jurnal Ilmiah Mahasiswa FIB, 2014)
Pratiwi, Anggit. 2013.  Speech Styles Performed by the Hosts of Masterchef Indonesia Season 3 Cooking Talent Show. Study Program of English, Universitas Brawijaya. Supervisor: Emy Sudarwati; Co-supervisor: Muhammad Rozin.Keywords: Speech style, Hosts, Masterchef Indonesia season 3 Cooking Talent Show.This study investigates the speech styles performed by the hosts of Masterchef Indonesia season 3 Cooking Talent Show when they talk to the participants of the show. In this study,  the writer conducts two problems of the study which are: (1) What types of speech styles that are used by the hosts in “Masterchef Indonesia Season 3”? (2) What type of speech style that is mostly used in the show?  The main theory to answer the problems  of the study is the theory of speech style by Martin Joos (1967, cited in Broderick 1976) and also supporting theories of standard and non-standard of Bahasa Indonesia by Kridalaksana (1989) and Chaer and Agustina (2004) as the data of this study are in the form of Bahasa Indonesia.    This study uses qualitative document analysis since the data of this study are in the form of words rather than numbers, and uses the transcription of the hosts’ utterances to be analyzed. The data of this study are the hosts’ utterances in Masterchef Indonesia season 3 the first episode containing speech styles.   Of the 5 (five) types of speech styles based on Martin Joos theory (frozen style, formal style, consultative style, casual style, and intimate style), the writer only found 3 (three) of them. They are formal style, consultative style, and casual style. The type of speech styles that were mostly used by the hosts consultative style in 95 (ninety three) utterances or 66%, followed by casual style in 31 (thirty one) utterances or 21,5%, and the last is formal style in 18 (eighteen) utterances or 12,5%. The findings showed that the hosts preferred not to use frozen style since this show was more semi-formal show and also did not use intimate style since the relationship between the hosts and the participants was not extremely close.    Finally, the writer suggests the next researchers to investigate the further study of speech style in the real society since there are so many objects in the surrounding society that can be  conducted. The writer also suggests the next researchers to explore more theories and the newest theory of speech styles to gain more understanding for the further research about speech style.